ANALISIS KELAINAN GENETIK - Miftahul Khairani; Ade Sekar Anggraini; Ayu Riski Aulia; Fany Erlangga Saragih; Faritz Khairuddin (JURNAL ILMIAH NUSANTARA, 2024)
The purpose of the study was to analyze genetic disorders in humans based on 10 national and international based journals. This research method uses a literature review design. From the results obtained, the pure genetic disease found was Down syndrome, with a total of 13 cases in four years. Other diseases that can be influenced by genetic factors such as primary hypertension, asthma, and schizophrenia were also found in sig1nificant numbers.